Bulk and surface Rashba splitting in single termination BiTeCl - Gabriel Landolt; Sergey V Eremeev; Oleg E Tereshchenko; Stefan Muff; Bartosz Slomski; Konstantin A Kokh; Masaki Kobayashi; Thorsten Schmitt; Vladimir N Strocov; Jürg Osterwalder; Evgueni V Chulkov; J Hugo Dil (New Journal of Physics, 2013)
By angle-resolved photoemission spectroscopy (ARPES) we observe a giant Rashba-type spin splitting in the electronic bulk conduction and valence bands of the semiconductor BiTeCl. This material belongs to the group of bismuth tellurohalides BiTeX (X = Cl,Br,I) which are layered non-centrosymmetric materials with strong spin–orbit interaction. By photon energy-dependent ARPES, we separate the bulk and surface contribution of the electronic structure and show that the tellurium-terminated (0001) crystal surface hosts spin-split two-dimensional surface states. On the chlorine-terminated surface at the opposite side of the crystal no surface states are observed due to photon-induced surface chemistry.